On a general Hyers-Ulam stability result - Costanz Borelli; Gian Luigi Forti (International Journal of Mathematics and Mathematical Sciences)
In this paper, we prove two general theorems about Hyers-Ulam stability of functional equations. As particular cases we obtain many of the results published in the last ten years on the stability of the Cauchy and quadratic equation.